APLIKASI ARDUINO PADA SMARTSTICK BAGI PENYANDANG TUNA NETRA - Winarno Fadjar Bastari; Akhmad Solikin; Widodo Widodo (Universitas Islam Lamongan, 2023)
The development of science and technology is so rapid today, so that various ideas appear in the field of electronics. Then to help human life, we have tried to apply electronic technology to simple systems. This research is intended to examine the use of Smartstick (assisting stick) for people with visual impairments. So far it is known that walking aids for blind people are very simple, they do not use electronic devices. Furthermore, the Arduino application is applied to this tool, namely this stick is equipped with 3 sensors that operate 180°, then sound alarm, vibration and GPS. When a blind person approaches an object, the alarm will sound and inform the distance between the blind person and the object. With a sensor range of 180 degrees, objects that are below the middle and even above will be detected, so that the Smartstick user will be able to avoid the possible distance until the warning alarm goes offautomatically. Therefore, blind people don't have to worry about crashing into other unwanted objects.